Physician vaccination practices in mild to moderate inborn errors of immunity and retrospective review of vaccine completeness in IEI: results from the Canadian Immunization Research Network - Suresh, Sneha; Zafack, Joseline; Pham-Huy, Anne; Derfalvi, Beata; Sadarangani, Manish; McConnell, Athena; Tapiéro, Bruce; Halperin, Scott A.; De Serres, Gaston; M Pernica, Jeffrey; Top, Karina A. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background and objectives Safety and effectiveness concerns may preclude physicians from recommending vaccination in mild/moderate inborn errors of immunity (IEI). This study describes attitudes and practices regarding vaccination among physicians who care for patients with mild/moderate B cell or mild/moderate combined immunodeficiencies (CID) and vaccination completeness among patients diagnosed with IEIs. Methods Canadian physicians caring for children with IEI were surveyed about attitudes and practices regarding vaccination in mild/moderate IEI. Following informed consent, immunization records of pediatric patients with IEI evaluated before 7 years of age were reviewed. Vaccine completeness was defined at age 2 years as 4 doses of diphtheria-tetanus-pertussis (DTaP), 3 doses pneumococcal conjugate (PCV), and 1 dose measles-mumps-rubella (MMR) vaccines. At 7 years 5 doses of DTP and 2 doses MMR were required. Results Forty-five physicians from 8 provinces completed the survey. Most recommended inactivated vaccines for B cell deficiency: (84% (38/45) and CID (73% (33/45). Fewer recommended live attenuated vaccines (B cell: 53% (24/45), CID 31% (14/45)). Of 96 patients with IEI recruited across 7 centers, vaccination completeness at age 2 was 25/43 (58%) for predominantly antibody, 3/13 (23%) for CID, 7/35 (20%) for CID with syndromic features, and 4/4 (100%) for innate/phagocyte defects. Completeness at age 7 was 15%, 17%, 5%, and 33%, respectively. Conclusion Most physicians surveyed recommended inactivated vaccines in children with mild to moderate IEI. Vaccine completeness for all IEI was low, particularly at age 7. Further studies should address the reasons for low vaccine uptake among children with IEI and whether those with mild-moderate IEI, where vaccination is recommended, eventually receive all indicated vaccines.